Complex Relationship Between Mangrove Ecosystem Variables and Fish Assemblages at Maumere Bay, Indonesia. (April 2019) - Vincentius, A; Nessa, M N; Jompa, J; Saru, A
Abstract: The aim of this study was to examine the abundance and composition of fish assemblages in the mangrove ecosystems of Maumere Bay, Indonesia. The study was conducted from September 2017 − April 2018. Sampling was conducted at 7 stations, with three substations as sampling replicates. Mangrove condition variables were mangrove area and belt width, mangrove percentage cover, mangrove density and dominance. Fish community variables were the abundance of each fish species and taxonomic fish diversity. Mangrove condition variables were collected and analysed using spatial analysis and quadrat transect methods. Data on fish assemblages caught by three-layer trammel nets were analysed using PRIMER, to obtain similarity percentages, ANOSIM and nMDS plots. To determine the correlation between mangrove and fish variables, data was analysed by multivariate regression using XLSTAT software. Results showed that overall 38 species of fish were recorded, belonging to 36 genera and 30 families. Darat Pantai station had the highest area (134.35 Ha), mangrove density (3, 220 trees/Ha), and dominance (35.46 m 2 /ha), while Talibura station had the highest percentage mangrove cover (80.63%) and the highest mangrove belt width was found at Kampung Garam II/Wuring station (427.6 m). The analysis of similarities (ANOSIM) at significance level 0.1% showed significant between-site differences in both mangrove assemblage structure and fish assemblages. The highest similarity percentage for mangroves was at Talibura station (98.53%), and for fish assemblages at Kampung Garam II/Wuring station (46.91%). Multivariate regression analysis showed that two mangrove ecosystem variables, belt width and density, were positively correlated with fish assemblage abundance and diversity, the strongest correlation (R 2 = 0.279) being with mangrove belt width.